2016
DOI: 10.1159/000454669
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine in Renal Medicine: New Virtues of an Ancient Friend

Abstract: Colchicine is a plant-derived alkaloid that disrupts the cell microtubule system and accumulates in neutrophils, inhibiting neutrophil adhesion and recruitment. Colchicine has been used extensively in the prevention and treatment of gouty arthritis attacks, familial Mediterranean fever attacks and resultant AA amyloidosis, and recurrent pericarditis. Colchicine also disrupts the intracellular traffic of additional inflammatory and fibrosis mediators. Renal fibrosis is the final common pathway of chronic renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 99 publications
0
14
0
1
Order By: Relevance
“…We prefer the term tubulin-binding agents (MTdisassembling agents, antitubulins) (Chaldakov, 1982Chaldakov and Vankov, 1986) instead of term MT targeting agents (Lu et al, 2012). Thus, tubulin has been emerging as a promising target for new anti-inflammatory (Chaldakov, 1991(Chaldakov, , 2017Martinez et al, 2015;Yanev et al, 2016), anti-fibrotic (Chaldakov and Nikolov, 1975;Chaldakov and Kadar, 1978;Chaldakov, 1982Chaldakov and Vankov, 1986;Chaldakov et al, 1987;Solak and Siriopol, 2017) and anti-cancer (Lu and Chen, 2012) drugs.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…We prefer the term tubulin-binding agents (MTdisassembling agents, antitubulins) (Chaldakov, 1982Chaldakov and Vankov, 1986) instead of term MT targeting agents (Lu et al, 2012). Thus, tubulin has been emerging as a promising target for new anti-inflammatory (Chaldakov, 1991(Chaldakov, , 2017Martinez et al, 2015;Yanev et al, 2016), anti-fibrotic (Chaldakov and Nikolov, 1975;Chaldakov and Kadar, 1978;Chaldakov, 1982Chaldakov and Vankov, 1986;Chaldakov et al, 1987;Solak and Siriopol, 2017) and anti-cancer (Lu and Chen, 2012) drugs.…”
Section: Figurementioning
confidence: 99%
“…From Chaldakov (1982) and . 1-3, [Chaldakov and Nikolov, 1975;Chaldakov and Vankov, 1986;Chaldakov et al, 1987;); also see Chaldakov et al, 1989;Solak and Siriopol, 2017). Preliminary proof for the possible anti-secretory (anti-fibrotic) effect of colchicine was presented in a lecture delivered by the author at the International Symposium on Smooth Muscle of the Artery, held Heidelberg, Germany, October 1973, which was published in 1975 (Chaldakov and Nikolov, 1975).…”
Section: The Bulgarian Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] It has been used in reducing fibrosis in liver and kidney diseases. [8] Besides, it also has some anti-inflammatory properties. This anti-inflammatory property is related to drug's effect on polymorphonuclear leukocytes and monocyte chemotaxis, leukocyte adhesiveness, and also its effect on prostaglandin E, which suppresses the leukocyte function.…”
Section: Introductionmentioning
confidence: 99%
“…Colchicine treatment could decrease systemic inflammation (Akodad et al, 2017). Indeed, colchicine had antifibrotic effects in diabetic nephropathy (Solak et al, 2017). Finally, clinical data suggested that colchicine treatment could inhibit cardiovascular diseases, among others (Frommeyer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%